2021
DOI: 10.2514/1.j059606
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Aerodynamic Comparison of Active Camber Morphing and Trailing-Edge Flaps

Abstract: Unlike hinged flaps (e.g. ailerons, elevator and rudder), camber morphing devices vary camber distribution in a smooth and continuous way, resulting in aerodynamic efficiency improvements due to the absence sharp changes in airfoil camber. One such camber morphing concept, the Fish Bone Active Camber (FishBAC) device, has shown significant aerodynamic benefits when compared to a flap. In this work, a quasi-2D wind tunnel test was performed to investigate the aerodynamic performance of a FishBAC device and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…A maximum ∆C L ≈ 0.55 is observed in the linear region of the lift curve (i.e., for angles of attack of less than α < 10 • ), whereas a ∆C L ≈ 0.40 is observed at around stall. Additionally, it is seen that the point of minimum drag does shift with increasing camber deflections, which is consistent with the results observed by [24]. However, it is worth noting that these drag coefficient results vary significantly with the angle of attack, which is not expected in a 2D wind tunnel test.…”
Section: Results: Aerodynamic Forces and Momentssupporting
confidence: 87%
See 2 more Smart Citations
“…A maximum ∆C L ≈ 0.55 is observed in the linear region of the lift curve (i.e., for angles of attack of less than α < 10 • ), whereas a ∆C L ≈ 0.40 is observed at around stall. Additionally, it is seen that the point of minimum drag does shift with increasing camber deflections, which is consistent with the results observed by [24]. However, it is worth noting that these drag coefficient results vary significantly with the angle of attack, which is not expected in a 2D wind tunnel test.…”
Section: Results: Aerodynamic Forces and Momentssupporting
confidence: 87%
“…However, it is worth noting that these drag coefficient results vary significantly with the angle of attack, which is not expected in a 2D wind tunnel test. Two-dimensional drag coefficients should remain relatively unchanged with increasing pitch angle (at a given camber deflection) when the flow is attached (i.e., in the linear region of the lift curve), and then "spike" as the flow starts to separate and stall (see [24] for example). These drag results suggest the presence of 3D effects that standard wind tunnel corrections ( [33]) cannot correct.…”
Section: Results: Aerodynamic Forces and Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a consistently higher efficiency for the wing equipped with a morphing flap over a large range of angles of attack, resulting in a maximum of 40% enhanced L/D at AoA = 14 • . This result is also consistent with published numerical work, where up to 18% gains in aerodynamic efficiency was achieved for a similar morphing configuration[32] and an over 50% improvement in (L/D) was obtained for a quasi-2D FishBAC experimental study[33].…”
supporting
confidence: 91%
“…This is supported by a further study which compared the same morphing concept with a traditional unsealed configuration using both CFD and experimental methods, and results showed that up to 18% gains in aerodynamic efficiency is achievable [32]. Most recently, Rivero et al [33] performed a quasi-2D wind-tunnel test to investigate the aerodynamic performance of a FishBAC morphing flap and compare it with a hinged flap configuration. Experimental results showed that the quasi-2D morphing flap was able to produce an over 50% improvement in the lift-to-drag ratio (L/D) at moderate to high lift coefficients where the flap device is significantly deflected, and an at least 16% higher lift-to-drag ratio at all lift coefficients, even for the lowest deflection values (~10 • ).…”
Section: Introductionmentioning
confidence: 85%